CHIMERIC ANTIGEN RECEPTOR T CELLS: PAST, PRESENT, AND FUTURE - BM, NAGARAJ; DP, SHRUTHI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Chimeric antigen receptor T (CAR T) therapy, a type of anticancer cellular immunotherapy, is emerging expeditiously. Primarily reported in 1987, the concept of a chimeric T-cell receptor (TCR), which combines antibody-derived variable regions with TCR-derived constant regions, was then, followed by double-chain chimeric TCR (cTCR) and single-chain variable fragment receptor chimeric cell (referred to as “T-bodies,” the prototypes of modern CAR). The CAR construct, which incorporates both a costimulatory endodomain and the CD3ζ signaling endodomain, is classified as a second-generation CAR, and this later achieved fantastic success in human clinical trials, marking a momentous milestone in the development journey of the CAR T-cell therapy. Tisagenlecleucel was the first CAR T-cell therapy to be approved by the Food and Drug Administration (FDA) for treating pediatric and young adult acute lymphoblastic leukemia. Six CAR T-cell therapies have been approved by FDA; many more are still there in the budding stages. The major challenges for CAR T-cell therapy are safety, ineffectiveness for solid tumors, cost, etc. To overcome these elements, further research is essential.